FEEDING BEHAVIOR AND FECUNDITY RATE OF SHRIMP SCAD ALEPES DJEDABA ALONG BALOCHISTAN COAST, PAKISTAN - A. Majeed; Z. Liang; C. Liu; L. Zhu; M. A. Kalhoro; K. H. Memon (Journal of Animal and Plant Sciences, 2022)
Shrimp scad Alepes djedaba is widespread in tropical waters and commercially important fish species of Pakistan. Feeding habits and fecundity rate were studied for A. djedaba from Balochistan, Pakistan. Total of 111 specimens were examined to perceive the feeding habits and 102 specimens for fecundity rate. Total of 16 ovaries were taken from stage four for estimation of fecundity rate. Frequency occurrence and numerical abundance were used to evaluate the feeding behavior. In frequency occurrence method different food items was observed. Fishes were found at 46% in guts, digested food at 34%, shrimp at 14% and shrimp larvae were found at 6%. While, fishes were observed at 48.74%, digested food at 33.17%, shrimps at 13.32% and shrimp larvae at 4.77% according to numerical abundance. These results show that A. djedaba is carnivorous in nature. The lowest fecundity rate was 8693 and highest rate was 73246, the average of fecundity rate of A. djedaba was found to be at 37220. Based on present findings it is evident that the fish has an extended spawning period throughout the year with a peak in July and August. The positive correlation (R2= 0.976) was observed between fish (weight) and fecundity rate during present study.
Keywords: Alepes djedaba; frequency occurrence; preponderance index; Gonadosomatic index